E. N. Gladden, A History of Public Administration - Izdebski, Hubert (Czasopismo Prawno-Historyczne, 1975)
Recenzja: E[dgar] N[orman] Gladden, A History of Public Administration, t. I, From Earliest Times to the Eleventh Century; t. II, From the Eleventh Century to the Present Day, London 1972, Frank Cass, ss. XII+270, XII + 420.